(untitled) - Kammeyer, Kenneth C. W; Ritzer, George (Boston, 1990)
Annotated instructor's edition; Includes bibliographical references and indexes; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: United States -- Social conditions; Hoa Kỳ -- Điều kiện xã hội; Social change; Thay đổi xã hội; Sociology; Xã hội học